Números e polinômios de Bernoulli - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2018)
In this work we study Bernoulli numbers and Bernoulli polynomials, as well as some of its most important applications in Number Theory. Based on a simple characterization, the Bernoulli polynomials are introduced and, later, the Bernoulli numbers. The Fourier series of the Bernoulli polynomials are used to demonstrate the functional equation of the theta function. This equation, in turn, is used in the proof of the famous functional equation of the zeta function, which is central to the theory of prime number distribution. In addition to the connections with the special functions zeta and theta, we also discuss, in detail, connections between the Bernoulli numbers and Bernoulli polynomials with the gamma function. These relations are then explored to produce beautiful formulas for certain values of the zeta function,among other applications.
Keywords: Números de Bernoulli; Polinômios de Bernoulli; Função Gama; Função Zeta; Função Teta; Equação Funcional; Bernoulli Numbers; Bernoulli Polynomials; Gamma Function; Zeta Function; CNPQ::CIENCIAS EXATAS E DA TERRA::MATEMATICA